Pengaruh Pengungkapan Tanggung Jawab Sosial Perusahaan, Debt to Equity Ratio dan Ukuran Perusahaan terhadap Manajemen Laba pada Perusahaan Trading Di Indonesia dan Filipina Tahun 2016-2020 - Lim, Tommy; Hendriyeni, Nora Sri (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
Companies that annually disclose CSR limit the occurrence of EM practices. A good DER is one with a low percentage, and a large SIZE will reduce the occurrence of EM. This study aims to see the effect of CSRD, DER, and SIZE on EM in trading companies in Indonesia and the Philippines in 2016-2020 and compare the results of each variable. The theory used is agency and stakeholder theory. The method to measure in the study using multiple regression analysis. Dependent Variables: EM, Independent Variables: CSRD, DER, and SIZE, research data were taken from 2016–2020 on trading companies in Indonesia and the Philippines, sampling using purposive sampling 70 data will be sampled in the study. The results of this study see that CSR in trading companies in the Philippines has a significant effect in reducing the occurrence of EM practices, while in Indonesia, it has no effect. DER has no impact on EM in both countries, SIZE in Indonesia has a negative impact on EM, and SIZE has no effect on EM in the Philippines.